Avaliação dos conhecimentos sobre a Medicina do Sono dos alunos da UNIFESP e do Instituto do Sono por meio do questionário ASKME - CONWAY, SILVIA GONÇALVES [UNIFESP] (2008)
Background: Despite its high prevalence and deleterious consequences to health, sleep disorders remain not well recognized by the medical community, indicating the need of implementing sleep medicine’s education. The investigation of basic knowledge on sleep medicine among physicians and medical students is restricted to a few studies, especially regarding evaluation prior and following educational intervention in sleep-related topics. Objective: This study intended to translate and adapt to Portuguese the ASKME questionnaire as well as to assess the psychometric properties of the translated version. The purpose of this instrument was to measure the impacts of educational intervention on sleep related topics provided by UNIFESP and the Sleep Institute; and to assess the differences between physicians trained in sleep medicine and the groups of students submitted to the educational intervention on sleep related topics from both institutions. Method: Translation and adaptation to Portuguese of ASKME questionnaire. Two applications, before and after sleep classes, were conducted with undergraduate students from 2nd year (104) and 3rd year of medical school (19), 4th year of nursing school (37), 2nd year of biomedical school (22), and graduated students obtaining master or PhD degree (38). One single application was performed with trained physicians in sleep medicine that had already concluded its specialization course (42) and with lay people (40). Registered polysomnographic technologists (23) also answered the ASKME and students from the training program in polysomnography technique (basic level) (100). Reliability analysis and item analysis were performed. Discriminative capability was evaluated comparing scores obtained by trained physicians with the international group of 75 accredited sleep experts, with lay people and with the medical students in 2nd year (prior to sleep classes). Instructional sensibility was assessed within the groups submitted to educational intervention through the pre-to-post test differences in knowledge score and by the Effect size index calculation. Differences in sleep knowledge between trained physicians and students submitted to the educational interventions were also analyzed. Pearson correlations tested the associations between total knowledge score and curricular time of learning. Results: The Brazilian version of ASKME demonstrated good internal consistency (Cronbach’s alpha = 0.84). Item difficulty ranged from 0.16 to 0.81 (mean = 0.50); item discrimination ranged from 0.01 to 0.67. Trained physicians’ performance on ASKME was statistically equivalent to the international group of sleep experts (84.0% vs. 85.3%) and was higher than lay people or 2nd year medical students (pre-test). Effect Size Indexes ranged from 1.0 to 2.6 depending on the group studied. Post test scores were higher than pre test on 2nd year medical students (10.2 + 4.5 vs. 16.8 + 3.4), 3rd year medical students (13.4 + 2.8 vs. 18.3 + 2.8) 2nd year biomedical students (9.6 + 3.4 vs. 16.1 + 2.8), 4th year nursing students (9.5 + 2.7 vs. 16.6 + 3.4), graduated students (13.5 + 6.0 vs. 19.2 + 3.1), and students from polysomnography technique training (basic level) (9.4 + 4.9 vs. 16.1 + 3.4) (all p<0.05). All groups presented lower total knowledge scores in comparison with trained physicians. Total knowledge score was correlated to curricular time of learning (r = 0.41; p < 0.01). Conclusions: ASKME questionnaire appears to be a reliable tool for assessment of sleep knowledge among different academic health segments and for evaluation of effectiveness of educational intervention in sleep medicine.